Anomalonine Wasps of the Genus Agrypon (Hymenoptera, Ichneumonidae) from Ukraine - Nuzhna, A.D (Вестник зоологии, 2013)
A key to the 12 species of the genus Agrypon Forster recorded from Ukraine is given. Some additional invariable characters such as morphometric index CI of the forewing, the presence of the small concavity on the anterior margin of mesoscutum and the metasternal tooth on propodeum are used in the key.